(3JMhd GdeUGQa GdJbdjOjI Gdi eUGQa GSdGejI ai VhA GMcGe GdTQjYI GdESdGejI (B/ s - (3YHjO Ydi YHjOs; (3jhSa eMehO bGSes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JCNP CTcGd GdJMhd GdPi JSdcg GdeUGQa GdJbdjOjI fMh GdYed GdeUQai GdESdGei Tcdjf GdChd gh GdJMhd Gdcdi hgh JMhjd LejY CYeGd GdeUQa hYedjGJg dJchf NGVYI dCMcGe GdTQjYI GdGSdGejI hGdKGfi GdJMhd GdLRFi HaJM fGaPI ChJMhjd aQY Gh GcKQ ef aQhY GdHfc GdJbdjOi djNUU dJbOje GdNOeGJ GdeUQajI GdeJhGabI eY CMcGe GdTQjYI GdESdGejI Ch WQM UfGOjb GSJKeGQjI ESdGejI hPdc HLGfH GdNOeGJ GdeUQajI GdJbdjOjIs
(3GWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdESdGejI, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B304-324s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3TQjYI ESdGejIs; (3GMcGe GdTQjYI GdESdGejIs; (3GdeUGQa GdESdGejIs; (3GdeUGQa GdJbdjOjIs; (3GdJMhd GdLRFj hGdcdj ddeUGQa GdJbdjOjI fMh GdeUGQa GdGSdGejIs; (3Mce GdJYGed eY GdfhGaP hGdaQhY GdESdGejIs; (3UfGOjb GdGSJKeGQ GdGSdGejIs; (3eUQa GdTGQbI GdGSdGejs; (3GdJNdU ef BKGQ GdeYGedGJ GdQHhjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3TQjYI ESdGejIs